Doing ethnography today theories, methods, exercises - Campbell, Elizabeth 1962-; Lassiter, Luke E. 1968- (Wiley-Blackwell, 2015)
"Provides guidance on interview questions and selecting appropriate field equipment"..
Includes index
Keywords: SOCIAL SCIENCE / Anthropology / Cultural; Ethnology -- Handbooks, manuals, etc; Ethnology -- Study and teaching; Ethnomethodologie; Ethnologie; Einführung